Feeding strategies and associated cognitive capacities among Plio-Pleistocene hominins: toward new perspectives using the ventromedial prefrontal cortex - Margot Louail (Revue de Primatologie)
Feeding and foraging behaviors can exert selective pressures among heterotrophic organisms that lead to morphological, physiological, and/or behavioral adaptations. Several studies showed that primates use complex cognitive abilities to adjust foraging strategies taking into account specific spatio-temporal context and already experienced events. Thus, it has been suggested that complex foraging strategies had a strong influence on the evolution of some cognitive abilities among primates, such as value-based decision-making. Following recent results showing that a cortical area, the ventromedial prefrontal cortex (VMPFC), is strongly associated with value-based decision-making, we previously explored the relationship between this region and ecological parameters (such as daily path length, mean group size, dietary quality) in extant primates. Among the five species studied (Macaca mulatta, M. fuscata, Gorilla gorilla, Pan troglodytes and Homo sapiens), those with broader diets and more complex foraging strategies exhibit a bigger VMPFC than species with a less diversified diet. We suggested that the capacity to switch foraging behaviors using memorized information may have been particularly favored among hominins of the Late Pliocene and especially Early Pleistocene, a period marked by several time intervals of increased climatic instability. Indeed, as these hominins faced critically changing environments, the ability to switch foraging behaviors and to fall back on alternative resources during periods of food scarcity probably played a strong influence on their diversity and evolution. This paper discusses the potential of a focus on the VMPFC to provide new insights into the evolution of foraging strategies and associated cognitive abilities (such as value-based decision-making) among hominins. As endocranial casts are the only available material to study brain anatomy on fossils, possible ways to measure this region from external cerebral markers are discussed.